Provable security : 9th International Conference, ProvSec 2015, Kanazawa, Japan, November 24-26, 2015, proceedings /: 9th International Conference, ProvSec 2015, Kanazawa, Japan, November 24-26, 2015, proceedings. (2015) - Unknown
No abstract available